Genealogical obscurement: mitochondrial replacement techniques and genealogical research - Palacios-González, César (Journal of medical ethics, 2025)
Mitochondrial replacement techniques (MRTs) are a new group of biotechnologies that aim to aid women whose eggs have disease-causing deleteriously mutated mitochondria to have genetically related healthy children. These techniques have also been used to aid women with poor oocyte quality and poor embryonic development, to have genetically related children. Remarkably, MRTs create humans with DNA from three sources: nuclear DNA from the intending mother and father, and mitochondrial DNA from the egg donor. In a recent publication Françoise Baylis argued that MRTs are detrimental for genealogical research via mitochondrial DNA because they would obscure the lines of individual descent. In this paper, I argue that MRTs do not obscure genealogical research, but rather that MRT-conceived children can have two mitochondrial lineages. I argue for this position by showing that MRTs are reproductive in nature and, thus, they create genealogy.